Proposed Strategy and Implementation of Bonchon Chiken Indonesia - Fadia, Dina; Wandebori, Harimukti (Journal of Business and Management, 2014)
The main of this research is identifying the competitor, current market condition and analyzing best strategy of Bon Chon. The author used several techniques of data analysis in this research for the data qualitative in this research was gathered through interview and observation. The result of the qualitative data will be conducted by using Industry Analysis, SWOT Analysis, and Value chain Analysis. And for quantitative data, questionnaire analysis will be conducted by using SPSS to test reliability and validity the questionnaire first. And then will be conducted by using multi dimensional scaling to know consumer perception between Bon Chon and other brands fast food, the author takes Kychon, Lotteria, and KFC for the competitors to compare with Bon Chon. The aim in this research is to identifying the current market condition or situation Bon Chon in fast food Industry and to know the characteristic of consumer Bon Chon. Nowadays Fast food has become part of people's lives in this modern era and IndonesiaÃ¢â‚¬â„¢s young generation currently has been influenced by foreign cultures (Western culture). On the other hand, the phenomenon of a new trend of fast food is regarded as a form of mass culture. As time goes by, the demand on Fast Food increase dramatically and all the fast food restaurant in Indonesia started to expand their market by open more outlets in many big cities in Indonesia. However, the trend changes rapidly and it makes the competition in fast food Industry become higher. Nowadays, many Indonesian people being a big fan of Ã¢â‚¬Å“Korean styleÃ¢â‚¬Â and it becomes an opportunity for Korean Fast food Industry to enter the Indonesian market. the result Bon Chon is using the competitive strategy to compete with competitors and still sustain this industry. Although that happened that strategy its not enough, Bon Chon also have to use a focus strategy in their competitive strategy techniques with making new target segmentation for increasing sales and developing the market in Indonesia. In the current condition target market of Bon Chon is middle to upper and doesnÃ¢â‚¬â„¢t has specification of their segmentation variables such as psychographic, demographics and geographic. And the key strength of Bon Chon is uniqueness of Product its proven by the result of questionnaire that 41.8% strongly agree and 36.9% agree with that statement.